Do Learning and Development Interventions Motivate Employees at PT Danone Indonesia? Applying McClelland’s Theory of Motivation to FMCG Industries - Maria Jacinta Arquisola; Sabiqa Uqda Walid Ahlisa (President University, 2019)
This research aimed to determine whether there is a relationship between employee motivation and learning and development programs at one of Indonesia’s biggest FMCG companies, PT Danone Indonesia. Guided by McClelland’s Theory of Motivation, three independent variables were analyzed relative to learning and development: the need for achievement, the need for power, and the need for affiliation. The research used quantitative method through a survey to gather data from 105 participants working at PT Danone Indonesia who, at the time of the study, had recently joined a series of learning and development programs. Data was analyzed using multiple regressions analysis. Findings show that employees are motivated to undergo learning and development because they want to fulfill two motivational needs: the need for power, and the need for achievement, the former being the highest motivator. On the other hand, the need for affiliation was not a strong motivator to encourage them to learn and develop. Results also show that the interest for learning and development could be explained by 42% of the variables. Implications for research and practice are discussed.